Is Diversity Still a Good Thing? - Herring, Cedric (American Sociological Review, 2017)
In this reply to Stojmenovska, Bol, and Leopold's comment on my 2009 ASR article, "Does Diversity Pay?" I offer an updated analysis of the relationship between racial and gender diversity in business organizations and such business outcomes as sales revenue, number of customers, market share, and relative profits. Despite the claims in their comment, an updated analysis supports the business case for diversity perspective. Racial and gender diversity are related to business outcomes in the direction predicted. I conclude that diversity is still a good thing, not just because it is related to business outcomes, but also because it reinforces the belief that everyone deserves an equal opportunity.